COST-EFFECTIVENESS ANALYSIS OF TREATMENT IN GASTROESOPHAGEAL REFLUX DISEASE INPATIENT PATIENTS IN BANDUNG, INDONESIA - TANJUNG, RIANI; WARDATI, YULIA; YULIANINGSIH, YUYUN; WIDYAWATI, IDA ERNA; MUSTARICHIE, RESMI; SAPTARINI, NYI MEKAR (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to analyze the cost-effectiveness of the GERD treatment management strategy for class II inpatient patients at a police hospital in Bandung, Indonesia. Methods: This study was retrospective, using medical record data collection techniques for 103 patients of the Social Security Administrator for Health (Badan Penyelenggara Jaminan Sosial, BPJS), from January 2017 to July 2019. The pharmacoeconomic method was Cost-Effectiveness Analysis. The medicines being compared were omeprazole injection and pantoprazole injection. The outcome parameter was the length of stay (LOS). The perspective was a hospital with a direct cost component. This study uses a 5% discounting rate due to differences in years. Results: The results showed that the patient majority was female (76%) and the largest age group was>40 y (53%). There was a significant difference in LOS and total cost between omeprazole and pantoprazole (p-value<0.050) using the Mann-Whitney test. The cost-effectiveness ratio showed that omeprazole has a higher value than pantoprazole. Conclusion: Therapy using pantoprazole was more cost-effective than omeprazole.